Honey Dressing Intervention with Diabetic Foot Ulcer: Systematic Review - Purnama, Agus; Prasetya, Ganjar Kundi; Andini, Amelia; Rohani, Rohani; Haryanti, Noviana; Isnaani, Ria Mariatul; Rayasari, Fitrian (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Diabetic foot ulcers are one of the complications of diabetes mellitus that are often suffered by patients with a history of diabetes mellitus in addition to complications in the form of retinopathy. The purpose of this study was to collect appropriate types of therapy for wound care in diabetic foot ulcer patients. This study uses a systematic review approach. Article search was limited to inclusion criteria and exclusion criteria. The inclusion criteria in this study were diabetic patients with diabetic foot ulcers. The conclusion in this study is that honey is very effective for wound healing in diabetic foot ulcer patients, although there are several methods that are quite effective besides honey, namely the Vacuum Closing package (negative pressure wound care). Honey has been shown to reduce wound size and heal wounds